Upaya Pencegahan Anak dari Pengaruh Minuman Keras Dihubungkan dengan Undang-Undang Nomor 35 Tahun 2014 Tentang Perlindungan Anak: Tinjauan - Dudu Duswara M; Dani Durahman (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
The current rise in alcoholic trade, in small roadside stalls, even among them has been openly trading alcohol. This results in the ease with which people get liquor. Including the alcoholic trade which is not accompanied by knowledge of the type of alcoholic beverage itself. Many of them do not understand the type of alcohol they can drink or not. Circulation of liquor at this time has not been handled properly, due to the lack of law enforcement against liquor sellers, so that with the easy sale of liquor that is still running it results in children who participate in becoming consumers and consuming liquor so that it has a negative impact on child growth and development. The number of alcoholic parties is certainly not just happening, the ease of people getting liquor makes some people easily drink alcohol. If we look at a number of events, this alcoholic party is carried out by a group of elderly people to high school children who are only a dozen years old. This happens because people can buy liquor easily at convenience stores. The ease of access to liquor is then one of the factors supporting the many alcoholic party events in the community. Another supporting factor from the rise of alcoholic parties in the Cigending Village community is the circulation of illegal alcohol in the community. One of the behaviors of children who reach adolescence is to show their true identity to friends or the environment, with environmental behavior that is not good and is not well cared for by the family can be excessive. In general, teenagers want to be recognized and get special treatment. Negative relationships that influence the use of liquor among teenagers. Liquor can damage the development of child development so there is a need for efforts to protect children from the bad influence of hard miniman as an effort to implement Law No. 35 of 2014 concerning Child Protection. The task of controlling this is in accordance with what is mandated by the Food Law, where the National Police has the right and obligation to control illegal alcoholic drinks without permission in accordance with applicable laws and regulations. Efforts to control illegal alcoholic beverages will greatly affect the decline in the incidence of alcoholic drinks because according to several events, people who carry out alcoholic drinks are usually from the lower middle class